Gestão ambiental em cadeias de suprimentos: Perspectivas atuais e futuras de pesquisa - Jabbour, Ana Beatriz Lopes de Sousa [UNESP]; Arantes, Ariana Fernandes [UNESP]; Jabbour, Charbel José Chiappeta [UNESP] (My University, 2013)
This article aims to identify the main definitions, practices and related avenues for future research on green supply chain management (GSCM). From a systematic literature review and analysis in major journals related to the topic and indexed in Scopus, was possible: a) identify key research goals of the articles analyzed, b) the research methodology adopted, c) the predominant industrials sectors studied, and d) the practices of GSCM considered relevant by researchers. Results are presented in each of these analytical perspectives. These results may be useful both for those interested in environmental management and in supply chain management, in view of the growing interest in GSCM.
Green supply chain management : Current and future prospects for research